1998
DOI: 10.1523/jneurosci.18-22-09256.1998
|View full text |Cite
|
Sign up to set email alerts
|

Slow Oscillations (≤1 Hz) Mediated by GABAergic Interneuronal Networks in Rat Hippocampus

Abstract: Perfusion of rat brain slices with low millimole CsCl elicits slow oscillations of Յ1 Hz in hippocampal CA1 pyramidal neurons. These oscillations are GABA A receptor-mediated hyperpolarizations that permit a coherent fire-pause pattern in a population of CA1 neurons. They can persist without the activation of ionotropic glutamate receptors but require adenosinedependent inhibition of glutamate transmission. In response to external Cs ϩ , multiple interneurons in the CA1 region display rhythmic discharges that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 78 publications
4
63
1
Order By: Relevance
“…Previously, GABAergic interneurons had been shown to inhibit themselves or other GABAergic neurons to promote disinhibition [6]. This study complements the previous studies by providing interesting findings of a slow oscillation in CA1 principal cells and interneurons mediated by GABA A receptors [7]. This work reveals important aspects of the interneuron circuit for generating slow oscillations and provides insights for understanding GABAergic transmission in hippocampal networks.…”
supporting
confidence: 78%
“…Previously, GABAergic interneurons had been shown to inhibit themselves or other GABAergic neurons to promote disinhibition [6]. This study complements the previous studies by providing interesting findings of a slow oscillation in CA1 principal cells and interneurons mediated by GABA A receptors [7]. This work reveals important aspects of the interneuron circuit for generating slow oscillations and provides insights for understanding GABAergic transmission in hippocampal networks.…”
supporting
confidence: 78%
“…The non-selective K IR antagonist Cs + induces the appearance of epileptiform activity in the CA1 area of hippocampal slices, suggesting that K IR plays a crucial role in controlling resting excitability in the hippocampus (Zhang et al, 1998;Andreasen et al, 2007). Here, we have shown that concentrations of Ba 2+ that selectively block K IR (Kubo et al, 1993;Schoots et al, 1996) without affecting K M (Cloues and Marrion, 1996) can trigger spontaneous interictal-like events in the EC.…”
Section: Involvement Of K Ir In the Generation And Maintenance Of Cchmentioning
confidence: 65%
“…In deep non-REM sleep, which is prominent in conditions of high sleep propensity such as after sleep deprivation, the EEG slow oscillation Ͻ1 Hz is the main source of ␦ activity (Amzica and Steriade, 1998;Massimini et al, 2004). It is interesting to note that the generation of the slow oscillation in rat hippocampal brain slices was shown to require an adenosinedependent inhibition of glutamatergic transmission (Zhang et al, 1998). Nevertheless, it should be considered that our method reflects EEG power and not necessarily the slow oscillation in non-REM sleep.…”
Section: Discussionmentioning
confidence: 99%